Incentives and Children's Dietary Choices: A Field Experiment in Primary Schools - Michèle Belot; Jonathan James; Patrick J. Nolen (Institute for the Study of Labor (IZA), 2015)
We conduct a field experiment in 31 primary schools in England to test the effectiveness of different temporary incentive schemes, an individual based incentive scheme and a competitive scheme, on increasing the choice and consumption of fruit and vegetables at lunchtime. The individual scheme has a weak positive effect whereas all pupils respond to positively to the competitive scheme. For our sample of interest, the competitive scheme increases choice of fruit and vegetables by 33% and consumption of fruit and vegetables by 48%, twice and three times as much as the individual incentive scheme, respectively. The positive effects generally carry over to the week immediately following the treatment but we find little evidence of any effects six months later. Our results show that incentives can work, at least temporarily, to increase healthy eating but there are large differences in effectiveness between schemes and across demographics such as age and gender.
Keywords: J13; I18; I28; H51; H52; 330; incentives; health; habits; child nutrition; field experiments